Disappearances in Mexico: from the "dirty war" to the "war on drugs" - Mandolessi, Silvana; Olalde, Katia (Europa country perspectives, 2022)
The Editors and ContributorsAcknowledgementsAcronyms and AbbreviationsIntroductionDisappearances in Mexico: From the 'dirty war' to the 'war on drugs'Silvana Mandolessi PART I Historical Dimensions of Disappearances1 Responsibilities in the system of enforced disappearance of people in Argentina: A historical perspectiveEmilio Crenzel 2 Recasting history to cast off shadows: State violence in Mexico, 1958-2018Eugenia Allier Montaño, Camilo Vicente Ovalle and Juan Sebastián Granada-CardonaPART II Political Dimensions of Disappearances 3 Disappearance and governmentality in MexicoPilar Calveiro4 Violence regimes and disappearances: Some reflections from the northeast region of MexicoKarina Ansolabehere and Álvaro MartosPART III Legal Dimensions of Disappearances 5 State acquiescence to disappearances in the context of Mexico's 'war on drugs'Lene Guercke6 Fate and whereabouts: the two elements that make up the right to know about the victims of enforced disappearanceRainer HuhlePART IV Affective and Experienced Dimensions of the Search and the Social Mobilization for the Disappeared 7 Pedagogies of searching in contexts of dispossessionCarolina Robledo Silvestre 8 The right to search in the case of disappeared persons: A right constructed from belowJorge Verástegui González9 Memorialising absence: Memorials to the disappeared in MexicoMaría de Vecchi GerliIndex